Habitat filtering on benthic meiofauna across tide pools and nearby sandy beaches - Coppo, Gabriel Carvalho; Netto, Sergio Antonio; Bernardino, Angelo Fraga (Frontiers in Marine Science, 2025)
IntroductionSpecies sorting by environmental gradients is an important driver of benthic meiofaunal biodiversity in marine ecosystems, but there are few attempts to test these effects in coastal habitats.MethodsIn this study, we evaluated the importance of habitat filtering in shaping meiofaunal communities across rocky tide pools and nearby sandy beaches in the Eastern Brazilian Marine Ecoregion, SW Atlantic. We proposed two hypotheses: (i) rocky tide pools exhibit a subset (nestedness effects) of the sandy beach meiofaunal assemblage, with lower phylogenetic diversity; and (ii) the meiofaunal assemblage composition and phylogenetic diversity vary seasonally over the year in both habitats. We used metabarcoding (V9 hypervariable region from 18S gene) from sediment samples (n = 70) to assess the meiofaunal assemblage composition and phylogenetic diversity, and tested spatial patterns of nestedness and turnover across habitats, seasons, and locations.ResultsCompared to the neighboring sandy beaches, tide pools had higher temperatures (+ 1.8°C) and lower quality organic matter. Contrary to our hypothesis, community turnover was the main driver of meiofaunal phylogenetic diversity and composition in both tide pools and nearby sandy beaches. The tide pool assemblages showed a lower phylogenetic diversity and taxon richness than the neighboring sandy beaches.DiscussionOur study supports the importance of environmental drivers on benthic meiofaunal phylogenetic diversity within tide pools and sandy beaches and revealed distinct assemblages in these neighboring coastal intertidal habitats.